2022
DOI: 10.1159/000525080
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Conducting Bring Your Own “Device” (BYOD) Clinical Studies

Abstract: <b><i>Background:</i></b> Digital health technologies are attracting attention as novel tools for data collection in clinical research. They present alternative methods compared to in-clinic data collection, which often yields snapshots of the participants’ physiology, behavior, and function that may be prone to biases and artifacts, e.g., white coat hypertension, and not representative of the data in free-living conditions. Modern digital health technologies equipped with multi-modal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…In fact, recent research demonstrated greater engagement with “bring-your-own device” clinical research as opposed to study-provided devices. Bring-your-own-device method potentially increase engagement because they tend to be more user-friendly and allow participants to use technologies that they are familiar with ( 41 , 42 ). Future research should examine whether our results generalize to this setting as well.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent research demonstrated greater engagement with “bring-your-own device” clinical research as opposed to study-provided devices. Bring-your-own-device method potentially increase engagement because they tend to be more user-friendly and allow participants to use technologies that they are familiar with ( 41 , 42 ). Future research should examine whether our results generalize to this setting as well.…”
Section: Discussionmentioning
confidence: 99%
“…DiME also hosts a library of digital endpoints used by registrational clinical trials [ 28 ]. A recent work was published to discuss the “bring your own device” (BYOD) option as a more user-friendly strategy to allow patients to use familiar technologies, which can ensure better compliance and unbiased measurements [ 29 ]. This is closely related to and applicable for a DCT.…”
Section: A Road Map To Dctmentioning
confidence: 99%
“…From a regulatory perspective, the risk-benefit for provisioned device versus BYOD is complex and requires careful consideration. 26,27 Wearable or connected device Wearable or connected devices include static or wearable devices that can support remote data collection directly from the participant (e.g. wearables like actigraphs that monitor activity levels) or their environment (e.g.…”
Section: Applications (Apps) and Technologymentioning
confidence: 99%